Social media usage: influence on student life / Wan Shahrul Aziah Wan Mahamad, Ramli Saad and Yong Azrina Ali Akbar - Wan Mahamad, Wan Shahrul Aziah; Saad, Ramli; Ali Akbar, Yong Azrina (Universiti Teknologi MARA, Kedah, 2023)
In today’s era of digital age, it has led to an increase of social media usage among everyone in the world, especially the younger generation. According to Boateng and Amankwaa (2016), social media can be said as an application that allows users to converse and interact with others who share similar personal or career interests, activities, backgrounds or real-life connections. Social media such as Facebook, Twitter, MySpace, Telegram, Linkedln, Instagram, WhatsApp, YouTube, and Tik Tok allows people to easily connect with each other, thereby making the world a global village. Nowadays, students are exposed to social media platforms on a daily basis; they use laptops computers, iPads, mobile phones and tablets to actively engage in social media platforms for chatting, blogging, content sharing, and online learning purposes. The exposure of social media has impacted students both in their academic and social life (Tayo et al. 2019). The following section will discuss the negative influence of using social media to student life.